Electrophoretic deposition of graphene-based materials: A review of materials and their applications - Yifei Ma; Jiemin Han; Mei Wang; Xuyuan Chen; Suotang Jia (Journal of Materiomics, 2018)
Recently, graphene-based materials have been successfully fabricated by the electrophoretic deposition (EPD) technique and exhibited various extraordinary properties. Here, research progress of the field of graphene-based materials prepared by the EPD process in recent 5 years is reviewed, including graphene films, graphene/non-metal composites, graphene/metal-based nanoparticles composites, graphene/polymer composites. We also summarize the experimental deposition conditions and the applications of the deposited graphene-based materials that have been reported. It can be concluded that EPD is a simple and reliable manipulation technique and promises a bright future for the production of graphene-based materials in the field of advanced nanocomposite materials. Finally the current issues and outlook of the development direction of EPD in future are also proposed. Keywords: Electrophoretic deposition, Graphene, Graphene-based composite materials, Applications